2002
DOI: 10.1093/hmg/11.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Premutation and intermediate-size FMR1 alleles in 10 572 males from the general population: loss of an AGG interruption is a late event in the generation of fragile X syndrome alleles

Abstract: We previously reported a 1:259 prevalence of female carriers of FMR1 premutation-size alleles (greater than 54 triplet repeats) in the general population. We now have screened 10 572 independent males from the same population for similar alleles using high-throughput Southern blotting. We identified 13 male carriers of an allele with more than 54 repeats. This corresponds to a prevalence of 1:813 males (95% confidence interval 1:527 to 1:1781). Haplotype analysis of four markers flanking the triplet array reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
225
6
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(248 citation statements)
references
References 34 publications
15
225
6
2
Order By: Relevance
“…Lanes 1 and 4, the two full-mutation alleles identified in this study; lanes 2 and 3, normal alleles identified in this study; lanes 5 and 6, normal and full mutation controls; lane 7, negative control. Canadian cohorts, 6,20 the value of 1/251 for premutation alleles is three times larger than the value of 1/813 previously reported in males by Dombrowski et al, 6 and is in close agreement with the expectation derived from the female Israeli cohorts. 8 The premutation alleles ranged in size from 55 to 77 CGG repeats; thus, all were toward the small end of the premutation range, again consistent with previous observations.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Lanes 1 and 4, the two full-mutation alleles identified in this study; lanes 2 and 3, normal alleles identified in this study; lanes 5 and 6, normal and full mutation controls; lane 7, negative control. Canadian cohorts, 6,20 the value of 1/251 for premutation alleles is three times larger than the value of 1/813 previously reported in males by Dombrowski et al, 6 and is in close agreement with the expectation derived from the female Israeli cohorts. 8 The premutation alleles ranged in size from 55 to 77 CGG repeats; thus, all were toward the small end of the premutation range, again consistent with previous observations.…”
Section: Resultssupporting
confidence: 87%
“…For example, in the screens of males and females in Eastern Canada, allele frequencies were estimated to be ϳ1/800 males and ϳ1/260 females. 4,6 However, in the Israeli studies, 3,7 the frequency of premutation alleles in women is closer to ϳ1/130. 7,9 By contrast, in an Asian (Taiwanese) population, the frequency of premutation alleles in males was reported to be much lower (ϳ1/1670).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Data reported in the literature show that IA present similar proportions of unstable transmissions. 25,26 In our series, 23 sequenced alleles had two or more AGG interruptions and 8 had none or only one AGG interruption, 6 of which remain stable in more than two generations. Even though the two IA that expanded to full mutation had lost the AGG interruptions, all alleles lacking an AGG interruption do not generally expand in the next generation.…”
Section: Discussionmentioning
confidence: 66%
“…27 The lack of AGG interruptions, together with other unknown genetic factors, probably contributed to repeat instability in the two cases as has been studied by Dombrowski and Morel. 26 A frequent concern in FXS screening is the genetic counselling to IA carriers. Currently, the follow-up of individuals with no AGG interruptions is indicated, despite the low risk of expansion in the next generation.…”
Section: Discussionmentioning
confidence: 99%